2023
DOI: 10.1021/acsmacrolett.3c00307
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterizations of Polythiophene Networks with Nonplanar BN Lewis Pair Building Blocks

Abstract: Doping the boron (B) element endowed organic π-conjugated polymers (OCPs) with intriguing optoelectronic properties. Herein, we introduce a new series of thienylborane-pyridine (BN) Lewis pairs via the facile reactions between thienylborane and various pyridine derivatives. Particularly, we developed a “one-pot” synthetic protocol to access BN2 with an unstable 4-bromopyridine moiety. Polycondensations between the BN Lewis pairs and distannylated thiophene afforded a new series of BN-cross-linked polythiophene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Recently, the strong binding of pyridines to triarylboranes has been exploited in the development of new robust COF materials with π‐conjugated structures [64] . For instance, Ren and co‐workers showed that complexes of tris(5‐bromothien‐2‐yl)borane with 4‐bromopyridine, 4,4′‐bipyridine or 1,3,5‐tris(pyridyl)benzene are amenable to Stille coupling polymerization with distannylated thiophene to produce COF materials with B−N LPs as crosslinking points [65] . The products showed interesting low energy ICT absorptions and one of the COFs was studied for photocatalytic H 2 production.…”
Section: Supramolecular Network Polymersmentioning
confidence: 99%
“…Recently, the strong binding of pyridines to triarylboranes has been exploited in the development of new robust COF materials with π‐conjugated structures [64] . For instance, Ren and co‐workers showed that complexes of tris(5‐bromothien‐2‐yl)borane with 4‐bromopyridine, 4,4′‐bipyridine or 1,3,5‐tris(pyridyl)benzene are amenable to Stille coupling polymerization with distannylated thiophene to produce COF materials with B−N LPs as crosslinking points [65] . The products showed interesting low energy ICT absorptions and one of the COFs was studied for photocatalytic H 2 production.…”
Section: Supramolecular Network Polymersmentioning
confidence: 99%
“…[64] For instance, Ren and co-workers showed that complexes of tris(5bromothien-2-yl)borane with 4-bromopyridine, 4,4'-bipyridine or 1,3,5-tris(pyridyl)benzene are amenable to Stille coupling polymerization with distannylated thiophene to produce COF materials with BÀ N LPs as crosslinking points. [65] The products showed interesting low energy ICT absorptions and one of the COFs was studied for photocatalytic H 2 production.…”
Section: Covalent Organic Framework Materialsmentioning
confidence: 99%
“…The high Lewis acidity of thienylborane towards various pyridine moieties (such as 4-bromopyridine, 4,4’-bipyridine, and 1,3,5-tri(pyridinyl)benzene) further inspired Ren and coworkers to design new thienylboran-pyridine (TB-py) Lewis pairs (Fig. 5a ) 71 . BN-crosslinked polythiophene networks with the diverse topological TB-py Lewis pairs were constructed by using typical Stille type coupling reaction (Fig.…”
Section: Introductionmentioning
confidence: 99%